The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2007
DOI: 10.1111/j.1600-0404.2007.00862.x
|View full text |Cite
|
Sign up to set email alerts
|

Sustained attention in cranial dystonia patients treated with botulinum toxin

Abstract: The results support the view that executive dysfunction in PCD is secondary to the disrupting effects of the symptoms. Treatment with BTX alleviates the symptoms and, consequently, improves sustained attention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
1
5

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 24 publications
0
42
1
5
Order By: Relevance
“…Attention deficit was reported by recent studies of patients with different types of dystonia, including primary generalized dystonia and focal dystonia (Allam, Frank, Pereira, & Tomaz, 2007; Scott et al., 2003). Attention deficit may indicate the disruption of the dorsolateral‐prefrontal loop, which involves the striatum, thalamus and prefrontal cortex, regions showing altered functional activity and microstructural abnormalities in dystonia (Yang et al., 2013; Zoons, Booij, Nederveen, Dijk, & Tijssen, 2011).…”
Section: Discussionmentioning
confidence: 85%
“…Attention deficit was reported by recent studies of patients with different types of dystonia, including primary generalized dystonia and focal dystonia (Allam, Frank, Pereira, & Tomaz, 2007; Scott et al., 2003). Attention deficit may indicate the disruption of the dorsolateral‐prefrontal loop, which involves the striatum, thalamus and prefrontal cortex, regions showing altered functional activity and microstructural abnormalities in dystonia (Yang et al., 2013; Zoons, Booij, Nederveen, Dijk, & Tijssen, 2011).…”
Section: Discussionmentioning
confidence: 85%
“…As previously suggested [2], some of these deficits may be related to the patients’ attempts to control their dystonia during cognitive testing. Supporting this, Allam et al [5] showed that improvement of blepharospasm following botulinum toxin was associated with significant improvement on a test of sustained attention.…”
Section: Introductionmentioning
confidence: 89%
“…Supporting this, Allam et al [5] showed that improvement of blepharospasm following botulinum toxin was associated with significant improvement on a test of sustained attention.…”
Section: Introductionmentioning
confidence: 89%
“…В отдельных исследованиях обнару-живается дефицит внимания у пациентов с цервикальной дистонией в сравнении со здоровыми пациентами [19]. После лечения ботулиническим токсином показатели внимания улучшались, что может свидетельствовать о вторичном характере этих расстройств, обусловленных дистоническим спазмом мышц [19]. Не исключено, что такие немоторные проявления дистонии, как боль и депрессия, также способствуют формированию дефицита внимания.…”
Section: когнитивные нарушенияunclassified